2023
DOI: 10.3390/polym15163418
|View full text |Cite
|
Sign up to set email alerts
|

End-Of-Use Fly Ash as an Effective Reinforcing Filler in Green Polymer Composites

Abstract: The aim of this study is to use fly ash powder in an environmentally friendly matrix, in a novel way, addressing environmental and disposal problems. Fly ash/epoxy composites were prepared and studied varying the filler content. An investigation of structural and morphological characteristics was conducted using of X-ray diffraction patterns and scanning electron microscopy images, which revealed the successful fabrication of composites. Thermomechanical properties were studied via dynamic mechanical analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The addition of mineral filler in the production of polymeric composites contributes to an improvement in mechanical resistance. Anastasios et al [12] added fly ash powder in various contents and found an increase in mechanical resistance as the ash content increased. In this way, the reuse of industrial waste for the development of artificial stones can be a solution to reduce the cost of this material, in addition to avoiding illegal disposal of solid waste, generating jobs and boosting the economy [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The addition of mineral filler in the production of polymeric composites contributes to an improvement in mechanical resistance. Anastasios et al [12] added fly ash powder in various contents and found an increase in mechanical resistance as the ash content increased. In this way, the reuse of industrial waste for the development of artificial stones can be a solution to reduce the cost of this material, in addition to avoiding illegal disposal of solid waste, generating jobs and boosting the economy [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, research on the impact of filler content and applied voltage under DC conditions has been conducted to evaluate the ability of composite materials to store and recover electrical energy. In particular, the inclusion of fly ash has shown an improvement in energy storage and recovery efficiency for these composite materials [25]. Another study explored the influence of basalt fiber and waste marble dust on epoxy resin.…”
Section: Introductionmentioning
confidence: 99%